2022
DOI: 10.1007/s10826-022-02465-0
|View full text |Cite
|
Sign up to set email alerts
|

Relations of Adolescent Knowledge of COVID-19, Social Media Engagement, and Experiences During Quarantine/Lockdown with Well-Being

Abstract: This study investigated the relations of adolescent COVID-19 knowledge, quarantine/lockdown experiences, and social media use with indices of their psychosocial adjustment. The sample consisted of 215 adolescents from throughout the United States, with adolescents ranging from ages 14 to 17. Better knowledge of COVID-19 was related to lower loneliness, stress, anxiety, depression, and fear of missing out (FoMO). Higher parent-reported restrictions during quarantine were associated with these difficulties as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Gender. Although in two studies, there were no significant differences observed between the mean FoMO-E scores according to gender [4,10], being a male was negatively correlated with FoMO [11]; similar results have been obtained by other researchers [9,12,13]. Only one of the reviewed studies decided to analyze the FoMO problem in transgender adolescents, showing that they obtained higher scores in the Comprehensive Inventory of Thriving subscale to assess loneliness and also the FoMO scores compared to cisgender females, cisgender males and combined group.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Gender. Although in two studies, there were no significant differences observed between the mean FoMO-E scores according to gender [4,10], being a male was negatively correlated with FoMO [11]; similar results have been obtained by other researchers [9,12,13]. Only one of the reviewed studies decided to analyze the FoMO problem in transgender adolescents, showing that they obtained higher scores in the Comprehensive Inventory of Thriving subscale to assess loneliness and also the FoMO scores compared to cisgender females, cisgender males and combined group.…”
Section: Discussionsupporting
confidence: 84%
“…[8] On the contrary, Santana-Vega et al in a group of 569 students aged from 12 -19, did not find differences between the mean of FoMO scores and age. [4] Similarly, in study in the USA examining possible links between COVID-19 knowledge and FoMO age was not correlated with the FoMO scores [9]. Gender.…”
Section: Discussionmentioning
confidence: 94%